Becoming art : exploring cross-cultural categories - Morphy, Howard (New York, NY : Berg, 2007)
'Becoming Art' provides a new analysis of the shifting cultural and social contexts that surround the production of Aboriginal art. Transcending the boundaries between anthropology and art history, the book draws on arguments from both disciplines to provide a unique interdisciplinary perspective that places the artists themselves at the centre of the argument. Western art history has traditionally regarded Aboriginal art as distanced from time and place. 'Becoming Art' uses the recent history of Aboriginal art to challenge some of the presuppositions of western art discourse and western art worlds. It argues for a more cross-cultural perspective on world art history.
Includes bibliographical references and index.
boek